2021
DOI: 10.1080/17524032.2021.1927129
|View full text |Cite
|
Sign up to set email alerts
|

The Loop Trail “Quest”: Use of a Choice-based Digital Simulation, An Interactive Video, and a Booklet to Communicate and Analyze Decision-making of Park Visitors

Abstract: Depreciative park visitor behaviors in protected areas can alter the relationship between humans, wildlife, and ecosystems and provide new opportunities for pathogens to cause illness in people. We created communication interventions that illustrate to park visitors the impact of off-trail walking, dogs off-leash, and littering. We aimed to uncover reasons behind park visitor decision-making and to compare differences in responses between messaging treatments. Our study in Great Falls Park (Potomac, MD) expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…A review of social theoretical frameworks and models included desk and literature reviews with reference to game-based learning, social theoretical frameworks, behavior change models, technological behavioral intervention models, DTC market approaches, and participatory ToC frameworks for complex interventions. Additionally, one of the authors (SH), the GOC Project Director, also provided evidence from her research on the application of game-based learning in One Health [ 35 ] to adapt those techniques to the development of the mobile game app. We conducted additional literature reviews of studies on consumer behavior models and frameworks most relevant to the game, to support the design of seamless DTC in-game elements.…”
Section: Methodsmentioning
confidence: 99%
“…A review of social theoretical frameworks and models included desk and literature reviews with reference to game-based learning, social theoretical frameworks, behavior change models, technological behavioral intervention models, DTC market approaches, and participatory ToC frameworks for complex interventions. Additionally, one of the authors (SH), the GOC Project Director, also provided evidence from her research on the application of game-based learning in One Health [ 35 ] to adapt those techniques to the development of the mobile game app. We conducted additional literature reviews of studies on consumer behavior models and frameworks most relevant to the game, to support the design of seamless DTC in-game elements.…”
Section: Methodsmentioning
confidence: 99%
“…Ten studies were either quasi-experimental or fully experimental. The two studies that were fully experimental were virtual and/or game-based, in which they presented dilemmas to respondents they had to resolve with a particular behavior [31,32]. The quasi-experimental studies typically examined waste disposal behavior where researchers would plant a study area with pieces of trash and observed number of trash items collected.…”
Section: Research Design and Methods Usedmentioning
confidence: 99%
“…Indirect management actions, by contrast, leverage communication interventions to minimize depreciative behaviors by influencing visitor reasoning and decision-making (Bradford & McIntyre, 2007; Brown et al, 2010; Gramann & Vander Stoep, 1986; Guo et al, 2015; Howard et al, 2021; Schwartz et al, 2018; Settina et al, 2020). Previous studies have suggested that most depreciative behaviors are the result of unintentional behavior, not of malicious intent, and that such behaviors could be remedied through education-focused communication interventional messaging (Eagly & Chaiken, 1993; Harrison, 1976; Marion & Reid, 2007; Namba & Dustin, 1992).…”
Section: Strategies and Tacticsmentioning
confidence: 99%